Augmented Reality in Secondary Science: Implementation, Evaluation, and Cognitive Learning Outcomes - Anggito Sulistyo Adi; Arrie Kurniawardhani (Komunitas Dosen Indonesia, 2026)
Science learning at the secondary school level remains challenging due to the abstract and complex nature of subjects such as physics, chemistry, and biology, which require advanced spatial and conceptual reasoning. Although Augmented Reality (AR) has increasingly been introduced to enhance visualization and interactivity in science classrooms, empirical evidence remains fragmented across implementation types, evaluation designs, and reported learning outcomes. Prior educational technology reviews rarely provide a focused synthesis explaining how specific AR implementation features relate to cognitive learning outcomes in secondary science education, leaving an important gap in understanding the pedagogical conditions under which AR becomes instructionally effective. This study systematically reviews recent empirical research on AR in secondary science education to identify dominant implementation patterns, examine evaluation approaches, and synthesize reported cognitive learning outcomes. A Systematic Literature Review (SLR) was conducted following Kitchenham’s guidelines and the PRISMA 2020 framework. Searches in ScienceDirect and Taylor & Francis Online identified 15 peer-reviewed studies published between 2020 and 2025 that met the inclusion criteria. A structured comparative synthesis categorized AR trigger mechanisms, media formats, and evaluation strategies to identify patterns linking implementation characteristics with learning outcomes. The results show that marker-based AR integrated with interactive three-dimensional models or simulations is the most common approach and is more consistently associated with positive cognitive outcomes. Studies employing structured pre-post or quasi-experimental designs reported clearer evidence of learning gains than those relying primarily on perception-based assessments. Overall, AR effectiveness appears to depend more on instructional design quality and rigorous evaluation methods than on technological novelty alone.